Diversity and Function of Microbial Community in Chinese Strong-Flavor Baijiu Ecosystem: A Review - Zou, Wei; Zhao, Changqing; Luo, Huibo (Frontiers in Microbiology, 2018)
Strong flavor baijiu (SFB), also called Luzhou-flavor liquor, is the most popular Chinese baijiu. It is manufactured via solid fermentation, with daqu as the starter. Microbial diversity of the SFB ecosystem and the synergistic effects of the enzymes and compounds produced by them are responsible for the special flavor and mouthfeel of SFB. The present review covers research studies focused on microbial community analysis of the SFB ecosystem, including the culturable microorganisms, their metabolic functions, microbial community diversity and their interactions. The review specifically emphasizes on the most recently conducted culture-independent analysis of SFB microbial community diversity. Furthermore, the possible application of systems biology approaches for elucidating the molecular mechanisms of SFB production were also reviewed and prospected.